Low back pain – a review - Rusiński, Kacper; Klimas, Filip; Zatłoka-Mazur, Dorota; Sienkiewicz, Michał; Pawłowski, Bartosz; Potoczek , Adriana; Zięba, Zuzanna; Pudełko , Iwona; Gajda, Zuzanna (Quality in Sport, 2025)
Low back pain (LBP) is a common condition affecting many individuals worldwide. Furthermore, it represents a significant economic challenge for healthcare systems due to its substantial associated costs. The etiology of LBP is complex but, in most cases, is not caused by serious underlying diseases. Physical examination remains the cornerstone of diagnosis, while additional tests, including imaging, are determined based on the clinical context. Treatment involves a combination of non-pharmacological, pharmacological, and invasive interventions. Despite numerous attempts to prevent LBP, only a few methods have been scientifically proven to be effective. The aim of this review was to provide a comprehensive summary of evidence-based information and approaches regarding the pathogenesis, treatment, and prevention of LBP. The literature reviewed was sourced from PubMed and Google Scholar Rusing the key words "low back pain" combined with terms such as "pathogenesis," "diagnostics," "imaging diagnostics," "treatment," and "prevention."